Exploration of Herpetofauna Habitat as Tourism Attraction: Ecology, Preferences, and Potentials - Kurniawan, Nia; Ananda, Alif Aulia; Kamila, Fatiha; Ardiantoro, Ari; Bagaskara, Satria Wira; Kurnianto, Agung Sih (Journal of Indonesian Tourism and Development Studies, 2018)
Herpetofauna (Class: Reptilia, Amphibia) has potential value as tourist attraction and its sustainability could be preserved by ecotourism program. We propose a new fauna-based tourism attraction by conducting herpetofauna survey in a few locations inside Sukamade, Meru Betiri National Park (MBNP), and using their habitat as spots for ecotourism potential sites. Visual Encounter Survey method was conducted in 6 locations (200 m transect pathway). We found 166 individuals, belonging to 32 species in 15 families. Leptobrachium hasselti has the biggest Important Value Index (16.55%), making this species potentially become one of the potential herpetofauna as a tourist attraction. Chelonia mydas, an endangered species, is one of the interesting species to be observed in Sukamade.This species is full migrant and does long migration in its feeding ground in Borneo, Australia, and Pacific, then back to Sukamade to lay eggs. Sumbersari and Glintungan forest became a habitat for amphibians that need clean water, such as L. Hasselti and Leptophryne borbonica, and potentially become the location of herpetofauna observation. Occidozyga lima, Fejervarya limnocharis, and Limnonectes microdiscus were found in four survey sites (Sumber Langsep, Glintungan, Estuary, and Jungle Track). Keywords: Herpetofauna, Sukamade, Tourism